Food Fraud and Risk Perception: Awareness in Canada and Projected Trust on Risk-Mitigating Agents. Issue 3 (3rd July 2017) - Charlebois, Sylvain; Juhasz, Mark; Foti, Lianne; Chamberlain, Sarah
ABSTRACT: During the past few years, food fraud has become a source of concern for consumers in many parts of the world. Major cases of food fraud have been found in Canada in recent months, including the Mucci case, in which Mexican tomatoes were sold as Canadian, as well as the case of a poultry farmer selling nonorganic chicken as organic. The authors aim to assess the level of awareness and trust among Canadian consumers in relation to fraudulent and counterfeit food products. This exploratory study is meant to establish latent determinants on consumers' risk perception of food fraud in general. These determinants include education, income, geographical region, age, sex, and health-related predisposition such as food allergies and intolerances. To this end, a random survey was conducted across Canada in January 2017. A sample size of 1088 was used for this study. Findings indicate that older, more-educated consumers generally feel more vulnerable, to various degrees, than do other consumers. Consumers who are aware and have experienced food fraud previously are likely to trust other consumers as risk-mitigating agents more so than public regulators or industry. Several limitations are presented, and future research paths are suggested.